2014
DOI: 10.2466/30.25.pms.118k19w4
|View full text |Cite
|
Sign up to set email alerts
|

Performance Indicators Analysis at Brazilian and Italian Women's Volleyball Leagues According to Game Location, Game Outcome, and Set Number

Abstract: This study was done to investigate the advantage of playing at home in elite women's volleyball leagues and the influence of performance indicators in the game score according to set number. The sample consisted of 240 games of the Brazilian Volleyball League (n = 132 games) and the Italian Volleyball League (n = 108 games) from the 2011-2012 season. The relationship of performance indicators (including serve, attack, block, and opponents' errors) with the game outcome (win or lose) was assessed. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 16 publications
0
14
0
4
Order By: Relevance
“…Early examples of research into performance factors include the study of Eom and Schutz (1992) analyzing matches from the third Federation of International Volleyball Cup men’s competition. In recent years, an increasing number of performance analysis studies focused on volleyball has been observed, aiming at finding correlations between different elements of the game and an increased chance of winning matches (Campos et al, 2014; Kountouris et al, 2015; Monteiro et al, 2009; Rodríguez-Ruiz et al, 2011; Silva et al, 2014). Similarly, some of them tried to predict the outcome of a game using some key variables and tailored mathematical and statistical formulas (Marcelino et al, 2011; Miskin et al, 2010; Peña et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Early examples of research into performance factors include the study of Eom and Schutz (1992) analyzing matches from the third Federation of International Volleyball Cup men’s competition. In recent years, an increasing number of performance analysis studies focused on volleyball has been observed, aiming at finding correlations between different elements of the game and an increased chance of winning matches (Campos et al, 2014; Kountouris et al, 2015; Monteiro et al, 2009; Rodríguez-Ruiz et al, 2011; Silva et al, 2014). Similarly, some of them tried to predict the outcome of a game using some key variables and tailored mathematical and statistical formulas (Marcelino et al, 2011; Miskin et al, 2010; Peña et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…An early approach was to count specific actions, which can give a general overview about differences between players or teams and can reveal valuable information about the strengths and weaknesses [3][4][5][6]. However, the analysis of single actions can only give a superficial insight into the tactical behaviour of teams.…”
Section: Introductionmentioning
confidence: 99%
“…3 Alguns estudos de voleibol indoor em diferentes faixas categorias e níveis competitivos, têm investigado a performance dos jogadores com objetivo de determinar fatores que resultam na melhor eficácia das ações técnicas nos treinamentos e competições. [4][5][6][7][8] Em geral, a eficácia no voleibol é controlada pelo sucesso em duas diferentes ações processuais: a primeira quando atinge diretamente o ponto (i.e: saque, bloqueio ou ataque) que é chamada de ação terminal e a segunda, quando uma ação não atinge o ponto diretamente (i.e: recepção, defesa ou levantamento) que é denominada como ações de continuidade. Essas particularidades da análise do jogo aplicada ao voleibol demonstram que as exigências ao nível do desempenho dos atletas e equipes, obrigam os treinadores a aprimorar os seus conhecimentos teóricos e práticos.…”
Section: Introductionunclassified
“…9 Ao mais alto nível competitivo, as habilidades técnicas que determina o resultado do jogo no voleibol são o ataque e o bloqueio. 10,7 Assim, os treinadores devem melhorar a qualidade da execução de habilidades que estão envolvidos em uma partida de voleibol, a fim de aumentar a eficiência técnica e a eficácia dos seus jogadores.…”
Section: Introductionunclassified